Biallelic mutations in LAMA5 disrupts a skeletal noncanonical focal adhesion pathway and produces a distinct bent bone dysplasia - Barad, Maya; Csukasi, Fabiana; Bosakova, Michaela; Martin, Jorge H; Zhang, Wenjuan; Paige Taylor, S; Lachman, Ralph S; Zieba, Jennifer; Bamshad, Michael; Nickerson, Deborah; Chong, Jessica X; Cohn, Daniel H; et al. (EBioMedicine, 2020)
BACKGROUND: Beyond its structural role in the skeleton, the extracellular matrix (ECM), particularly basement membrane proteins, facilitates communication with intracellular signaling pathways and cell to cell interactions to control differentiation, proliferation, migration and survival. Alterations in extracellular proteins cause a number of skeletal disorders, yet the consequences of an abnormal ECM on cellular communication remains less well understood METHODS: Clinical and radiographic examinations defined the phenotype in this unappreciated bent bone skeletal disorder. Exome analysis identified the genetic alteration, confirmed by Sanger sequencing. Quantitative PCR, western blot analyses, immunohistochemistry, luciferase assay for WNT signaling were employed to determine RNA, proteins levels and localization, and dissect out the underlying cell signaling abnormalities. Migration and wound healing assays examined cell migration properties. FINDINGS: This bent bone dysplasia resulted from biallelic mutations in LAMA5, the gene encoding the alpha-5 laminin basement membrane protein. This finding uncovered a mechanism of disease driven by ECM-cell interactions between alpha-5-containing laminins, and integrin-mediated focal adhesion signaling, particularly in cartilage. Loss of LAMA5 altered β1 integrin signaling through the non-canonical kinase PYK2 and the skeletal enriched SRC kinase, FYN. Loss of LAMA5 negatively impacted the actin cytoskeleton, vinculin localization, and WNT signaling. INTERPRETATION: This newly described mechanism revealed a LAMA5-β1 Integrin-PYK2-FYN focal adhesion complex that regulates skeletogenesis, impacted WNT signaling and, when dysregulated, produced a distinct skeletal disorder. FUNDING: Supported by NIH awards R01 AR066124, R01 DE019567, R01 HD070394, and U54HG006493, and Czech Republic grants INTER-ACTION LTAUSA19030, V18-08-00567 and GA19-20123S.
Keywords: laminin; Genetic Predisposition to Disease; alely; skupina kinas odvozených od src-genu; Chondrocytes; signální transdukce; Focal Adhesion Kinase 2; signální dráha Wnt; Cell Adhesion; src-Family Kinases; Alleles; Laminin α5; fokální adhezní kinasa 2; DNA Mutational Analysis; Bone and Bones; Signal Transduction; mutace; mutační analýza DNA; fenotyp; chondrocyty; Phenotype; kosti a kostní tkáň; Skeletal dysplasia; genetické asociační studie; Mutation; Humans; Laminin; β1 integrin; vývojové onemocnění kostí; Wnt Signaling Pathway; buněčná adheze; LAMA5; Genetic Association Studies; genetická predispozice k nemoci; Bent bone; Bone Diseases, Developmental; lidé